Swipe, Like, Buy: A Netnographic Study On The Impulse Buying Behavior In Tiktok Shop Ecosystem - Azhar, Andi (Universitas Dehasen Bengkulu, 2025)
This study investigates impulse buying behavior within the TikTok Shop ecosystem through a netnographic lens. As TikTok evolves into a dominant force in social commerce, it blurs the boundaries between entertainment and shopping. This research explores how algorithm-driven content, influencer marketing, live streaming, and user-generated interactions stimulate unplanned purchase decisions. Drawing on data collected from three months of online observation of Indonesian TikTok Shop environments, this study identifies key emotional, social, and technological triggers of impulse buying. The findings reveal a novel model of algorithm-induced impulsivity, contributing to consumer behavior theory and offering implications for marketers, platform designers, and digital literacy advocates.